Numerical Simulations on Quantum Noise Squeezing for Soliton-like Pulses in Optical Fiber - Sorokin, Arseny A.; Salnikov, Nikolay I.; Kosareva, Anna N.; Alyukova, Valeriya P.; Leuchs, Gerd (Proceedings of the International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD, 2022)
Generation of light with nonclassical properties, such as squeezed light, has gathered a lot of attention because of possible uses in such areas as quantum state engineering, quantum imaging, continuous variable quantum computing, and detection of gravitational waves. Squeezed light is generally produced by transporting light through a nonlinear medium. One such media is Kerr-nonlinear optical fibres. We aim to find the parameters for a fibre polarization squeezing setup by studying the dependencies of quantum noise suppression on the duration of the pulse and the input power. This is performed by modeling the light field propagation using the split-step Fourier method to numerically solve the stochastic nonlinear Schrödinger equation obtained by using the Wigner representation. This equation includes such physical effects as damping, quantum loss noise, dispersion, Kerr and Raman nonlinearities, and stochastic Raman noise.
CRIS-Team Scopus Importer:2023-04-20